Integrating SDGs into management: Guidelines for contributing to the United Nations Sustainable Development Goals (SDGs) - Arroyo-Vázquez, Natalia (Anuario ThinkEPI, 2024)
The International Organization for Standardization (ISO) published the Guidelines for contributing to the United Nations Sustainable Development Goals (SDGs), ISO/UNDP PAS 53002:2024, which seek to facilitate the integration of the SDGs in the management of all types of organizations, among which libraries, archives or documentation centers could be found. This document presents a comprehensive approach, which affects the entire organization and different stages of management, provide guidelines for planning that optimizes results in terms of SDGs and invite organizations to make a greater commitment to sustainability and equity. Two aspects of this document are worth highlighting: it suggests considering the environment, the planet, or future generations, among others, as stakeholders that may be influenced by the organization’s activities, and raise the need to evaluate the impact produced by the organizations and take it into account when making decisions.